Perspectives on the development and consumption of functional foods and their promotion in health: A scoping review - Arias Escobar, Jesús (2024)
The development and consumption of functional foods (FF) have gained relevance in response to modern dietary habits and their effects on public health. This study evaluated the current perspectives on FF in different countries and their promotion of health through a bibliometric and scoping review of the Scopus database, selecting 52 relevant documents from the last 15 years. The search equation used was ("functional food" or "functional product") and ("food development" and health) and not (animals or animals). The R biblioshiny package was used to quantify the data. The results revealed an increase in scientific research on FF, especially during the COVID-19 pandemic, due to the interest in strengthening the immune system. The research shows significant collaboration between countries, highlighting China, the United States, and Brazil as leaders and institutions such as Zhejiang University and the University of São Paulo as influential. Consumer acceptance of FF depends on factors such as ingredients, price, and sensory characteristics. Clear communication about the benefits and limitations of FF is essential for guiding food choices, along with the need for rigorous research and clinical trials to support their health properties. Although FF has a significant potential to improve health, promoting healthy eating habits remains fundamental to healthy overall well-being.